Sosialisasi Program LISA (Lihat Sampah Ambil) dalam Mewujudkan Kelurahan Bebas Sampah di Kelurahan Ngedukelu - Pare, Prisko Yanuarius Djawaria; Bela, Maria Editha; Wele, Agustina; Suri, Skolastika Mariana; Soko, Januarius Andreas; Loda, Maria Febrianti; Itu, Kristina Evanjelina; Meo, Fransiskus Xaverius; Ruju, Gabriel; Sadok, Stefanus Clarikus (LPMP Imperium, 2026)
The Ngedukelu Village Government faces low public awareness of household waste management, resulting in an unclean environment and potential negative impacts on health and sustainability. One simple effort to address this issue is implementing the LISA (See Garbage Pick Up) Program. This community service aims to foster socialization and instill environmental awareness among the community to realize a waste-free village. The method used in this activity is a participatory approach through direct demonstrations in collaboration with residents of Ngedukelu Village, involving 13 neighborhood units (RT) and 3 community units (RW). The activities include socialization, demonstration of proper waste management practices, and community engagement to build sustainable behavior. The results show that the implementation of the LISA Program has a positive impact on improving environmental cleanliness and increasing public awareness. The community has begun to adopt the habit of picking up scattered waste and maintaining environmental hygiene. Indicators of success include residents adopting the movement and the emergence of community initiatives to install trash bins in residential and public areas. In conclusion, this program effectively improves environmental conditions and fosters positive behavioral changes in waste management among the community of Ngedukelu Village.